STOP1 and STOP1-like proteins, key transcription factors to cope with acid soil syndrome - Li, Xinbo; Tian, Yifu (Frontiers in Plant Science, 2023)
Acid soil syndrome leads to severe yield reductions in various crops worldwide. In addition to low pH and proton stress, this syndrome includes deficiencies of essential salt-based ions, enrichment of toxic metals such as manganese (Mn) and aluminum (Al), and consequent phosphorus (P) fixation. Plants have evolved mechanisms to cope with soil acidity. In particular, STOP1 (Sensitive to proton rhizotoxicity 1) and its homologs are master transcription factors that have been intensively studied in low pH and Al resistance. Recent studies have identified additional functions of STOP1 in coping with other acid soil barriers: STOP1 regulates plant growth under phosphate (Pi) or potassium (K) limitation, promotes nitrate (NO3-) uptake, confers anoxic tolerance during flooding, and inhibits drought tolerance, suggesting that STOP1 functions as a node for multiple signaling pathways. STOP1 is evolutionarily conserved in a wide range of plant species. This review summarizes the central role of STOP1 and STOP1-like proteins in regulating coexisting stresses in acid soils, outlines the advances in the regulation of STOP1, and highlights the potential of STOP1 and STOP1-like proteins to improve crop production on acid soils.